The Role of Active Coping in the Relationship Between Learning Burnout and Sleep Quality Among College Students in China - Wang, Yi; Xiao, Huiwen; Zhang, Xiaotian; Wang, Li (Frontiers in Psychology, 2020)
Learning burnout negatively influences students’ learning and well-being. Sleep quality is directly related to students’ health and learning outcomes. Research indicates that sleep quality and coping style may be associated with learning burnout. However, the interrelationship among learning burnout, sleep quality, and coping style has not yet been fully studied. The study aims to explore the relationship between sleep quality and learning burnout and examine whether coping mediates the relationship between learning burnout and sleep quality in Chinese university students. A total of 228 undergraduate students were recruited to participate in this research. The Simplified Coping Style Questionnaire (SCSQ), Learning Burnout Questionnaire (LBQ), and Pittsburgh Sleep Quality Index-Chinese (PSQI-C) were employed to collect data. The results showed the following: (1) poor sleep quality had a positive association with learning burnout; (2) a positive coping style mediated the effects of poor sleep quality on learning burnout and the dimensions of learning burnout (emotional exhaustion and low sense of achievement). The three models in the SEM analyses showed good model fit. The findings of the current study contribute to knowledge of learning burnout and provide theoretical evidence for further educational interventions.